Emerging Technologies as Provocations for Theology and Ethics - Green, Brian Patrick (Theology and science, 2026)
Emerging technologies are provocations for theology and ethics, forcing theologians and ethicists to think more deeply about questions we might have thought were already answered. By delivering to humankind new powers and capabilities that none have previously had, new technologies raise for us questions of who we are, our place in the world, and what we should be doing. These technologies also raise for us questions about God, and why our universe is created the way it is, with latent opportunities for new technologies, including extraordinarily risky ones that could kill us all. Surveying roughly the last century of technological development, this paper examines many of these questions and what they might mean, especially for us who desire to respond.